2021
DOI: 10.3390/pharmaceutics13040465
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Olive Oil Industry By-Products Extracts with Potential Skin Benefits in Topical Formulations

Abstract: The by-products of olive oil industry are a major ecological issue due to their phenolic content, highly toxic organic load, and low pH. However, they can be recovered and reused, since their components have antioxidant, anti-inflammatory, and photoprotector properties. In this work, oil-in-water creams containing three different olive oil industry by-products extracts were produced without the use of organic solvents. First, the extracts were thoroughly characterized in vitro for cytotoxicity, inhibition of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…FucoPol was used to prepare emulsions with four different oils commonly used in cosmetic products' formulations, namely, castor oil [35][36][37][38], paraffin oil [39][40][41], almond oil [42,43] and olive oil [44][45][46][47][48]. Castor oil is a natural oil that acts as an antimicrobial, anti-inflammatory, antioxidant, wound healing, vasoconstrictive [49] and UV-protective agent [50].…”
Section: Preparation Of Fucopol-stabilized Emulsions With Different Oilsmentioning
confidence: 99%
“…FucoPol was used to prepare emulsions with four different oils commonly used in cosmetic products' formulations, namely, castor oil [35][36][37][38], paraffin oil [39][40][41], almond oil [42,43] and olive oil [44][45][46][47][48]. Castor oil is a natural oil that acts as an antimicrobial, anti-inflammatory, antioxidant, wound healing, vasoconstrictive [49] and UV-protective agent [50].…”
Section: Preparation Of Fucopol-stabilized Emulsions With Different Oilsmentioning
confidence: 99%
“…As matter of fact, formulation A (gray line) showed a reduction in dynamic viscosity (η) value as the shear rate (Ύ) increased (viscosity values range from 315.79 mPa•s to 151.030 mPa•s) (Figure 4a). This behavior is typical of non-Newtonian fluids, such as creams, gels, lotions, and emulsions [5,48]. The profile indicates the semi-flexible molecular structure of A, with a low flow resistance; aggregates are rapidly broken into their elements, the droplets lining up at a high shear rate supports the formulation's ability to spread on the skin [21].…”
Section: Rheological Assessmentsmentioning
confidence: 99%
“…Among exogenous antioxidants, natural derivatives, such as carotenoids and polyphenols are effective, widely present in plants, and potentially induce fewer side effects than synthetic ones [3,4]. There is great interest among researchers and industry in the recovery of antioxidant molecules from waste and by-products of the agri-food chains [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several natural molecules were recently proposed to exert a positive biological effect on human cell physiology. Although their role on human keratinocyte cultures has not been determined to date, it has been suggested that several components of the Olea europaea olive oil may be potentially beneficious for the skin due to their topical antioxidant effect ( Nunes et al, 2021 ). In fact, it has been demonstrated that olive oil extracts favor skin wound healing through NOS-2 and NFE2L2factors ( Schanuel et al, 2019 , 2).…”
Section: Introductionmentioning
confidence: 99%